The dark side of shareholder orientation: A reflection of Rappaport's concept of shareholder value - Florian Follert; Heinz E. Klingelhöfer; Frank Daumann (Managerial and Decision Economics, 2023)
The concept of shareholder value has been the subject of heated debate for 400.167emyears. Surprisingly, the literature seems to overlook the fact that shareholder orientation by management is something completely different from the implementation of this idea in the well-known shareholder value concept, which aims to measure the contribution of management to shareholder welfare. Using a market-oriented framework, this study shows that the fundamental orientation of shareholders' subjective preferences is supported by a property rights perspective inspired by the ideas of the Austrian School of Economics. In contrast, Alfred Rappaport's shareholder value concept is based on neoclassical equilibrium thinking and, therefore, counteracts the real, imperfect environment of the corporation's decision-makers, especially their subjective values. This results from individual preferences and decision parameters, as well as incomplete and asymmetric information. Thus, it ignores the reality of managerial decision-making. Based on these considerations, we argue that the advocacy of a general managerial orientation toward shareholders' objectives does not logically imply full support for the implementation of the idea under Rappaport's concept. In doing so, this essay contributes to a more differentiated discussion on valuation, corporate governance, and managerial decisions.
Keywords: 650